AIRWAY MANAGEMENT SIMULATION TRAINING FOR NOVICE NURSING STUDENTS: AN OBSERVATIONAL STUDY. (13th May 2015) - Kaur, Baljit
Abstract : Background/Purpose: Airway Management is one of the crucial skills to increase the survival chance of a critical patient. Nurses act as one of the team member during airway management. Nurses carry-out basic airway management and as an assistant in advanced airway management. Simulation had been commonly used to teach the skills of airway management in medical education. Hence, it can also‖be used in nursing education. This study aims to provide airway management simulation training to novice nursing students to improve their skills in performing the skill. Methodology: This is an observational study. Year three undergraduate nursing students were voluntarily recruited in a bachelor of nursing programme. They are equipped with basic skills of taking patients and are ready to take care of critical patient. Students will be divided into twenty groups (n=20) with three students in each group. They are provided with theoretical knowledge of airway management, demonstration, and hands-on practice on simulation. The same training was implemented twelve weeks later to assess the retention of knowledge. Results: Only 35% (n=7) were able to complete basic airway management in the first training and all of the students were able to complete it in the second training (n=20). None of the group were able to complete the airway management skills in the first trial and the completion rate in the second training increased to 65% (n=13). Students were having difficulty in manipulating and assemble the equipment. They were not able to identify their role and responsibilities as well. Conclusion and Recommendations: Simulation training in airway management is effective in helping novice nursing students in gaining the experience, knowledge and performance of the skill. Simulation training gives a real life experience of learning and hands-on skill practice is an important aspect in promoting learning and teaching.